Potential of biomass for bioenergy in Pakistan based on present case and future perspectives - Naqvi, S.R. (Elsevier Ltd, 2018)
Future energy security and environmental issues are major driving forces for increased biomass utilization globally and especially in developing countries like Pakistan. For efficient utilization of indigenous biomass resources in the future energy mix, it is important to gain knowledge of current energy system in various sectors. Some of the technologies and initiatives are under development to achieve transition from non-renewable resources to renewable resources, and reducing fossil fuel dependency and greenhouse gas emissions. Recently, number of proposals has been presented for the development of sustainable biofuels production methods for promise for accelerating a shift away from an unsustainable approach to possible sustainable production practices or a sustainable social, economic and environment. This article presents an extensive literature review of the biomass-based renewable energy potential in Pakistan based on current energy scenario and future perspectives. It also highlights the availability of the indigenous and local biomass resources and potential biomass conversion technologies to convert such resources to bioenergy. The drivers for utilization of indigenous biomass resources in future energy mix and challenges regarding awareness among stakeholders and R&D to fill knowledge gaps are economically restraints. The article concludes with suggestions on future directions and policies for effective implementation of biomass based renewable energy production. Â© 2017 Elsevier Ltd